Multi-sided platform and data-driven care research - Daniel Fürstenau; Stefan Klein; Amyn Vogel; Carolin Auschra (Electronic Markets, 2021)
Multi-sided platforms in healthcare often focus their business model on standardizing care for wide-spread, chronic diseases. However, there is a lack of knowledge surrounding platform business models enabling individualized care coordination for patients with rare diseases. This paper analyses the development of a complex platform business model addressing Amyotrophic Lateral Sclerosis, a severe neurological disease that requires the coordination of a diverse network of medical specialists, care, and equipment providers. A longitudinal case study examines the platform's development, focusing subsequently on qualitative and efficient care coordination, care research, and active and direct involvement of patients, as well as establishing two business models, namely, care coordination and care research. We reconstruct how these complex platform business models were configured to improve patient care and care research, thereby creating immediate value for patients and insights for long-term care improvements. The ongoing platform development carefully balances value generation for diverse stakeholders and economic sustainability.
Keywords: I1; M1; O3; 620; Digital health platform; Business model; Datafication; Value-based health; Rare disease; Care research; Process perspective